IMPLEMENTASI COOPERATIVE LEARNING (STAD) DAN GAYA KOGNITIF UNTUK MENINGKATKAN PRESTASI BELAJAR PADA MATA KULIAH KLINIK KEPERAWATAN - ATTI YUDIERNAWATI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
The main purpose of this study were to examine The effect of learning Strategy (cooperative Learning (STAD) vs Direct Instruction ) and cognitoi style on Learning Achievement of Nursing Clinical Study. This study used quasi experiment.The subject of this research were 88 students from the 2nd grade of III-Diploma Program Study of Malang Nursing Department. The data were collected using test cognitive style and learning achievement. The hypothesis were examined with two ways ANOVA The findings of the study were : (1). There is a difference in learning achievement between the students who were taught by using cooperative learning strategy and who were taught using direct instruction. 2). There is a different achievement in students with different cognitive style, and 3) There is no interaction between learning strategy and students’s cognitive styles toward learning achievement on nursing clinical subject matter. ABSTRAKTujuan penelitian adalah untuk mengidentikasi pengaruh ieraksi strategi pembelajaran , kooperatif learning (STAD) dan pembelajaran langsung serta gaua kognitif terhadap prestasi belajar mata kuliah klinik keperawatan. Desain penelitian menggunakan quasi eksperimen, seubyek penelitian sejumlah 88 mahasisea tingkat II Program Studi D-3 Keperawatan Malang. Pengumpulan data dilakukan dengan melakukan uji tes gaya kognitif mahasiswa dan dari hasil belajar. Analisis fata menggunakan uji Anova. Hasil penelitian menunjukkan 1) Ada perbedaan prestasi belajar antara mahasiswa yang menggunakan kooprtaif learning (STAD) dengan pembelajaran langsung. 2) Ada perbedaa hasil belajar antara mahasiswa antara gaya kognitf Field dependence dan field Independence, dan (3) Tidak ada interaksi antara strategi pembelajaran dan gaya kognitif terhadap prestasi belajar mata kuliah klinik keperawatan.